Paleogene post-collisional lamprophyres in western Yunnan, western Yangtze Craton: Mantle source and tectonic implications - Lu, Y.; Campbell McCuaig, T.; Li, Zheng-Xiang; Jourdan, Fred; Hart, C.; Hou, Z.; Tang, S. (Elsevier, 2014)
A suite of lamprophyres, spatially associated with mafic lavas and potassic felsic intrusive rocks, was emplaced between 36.5±0.2 and 33.7±0.5Ma (based on phlogopite 40Ar/39Ar dating) on the eastern side of the Ailao Shan-Red River shear zone in the western Yangtze Craton. These shoshonitic and ultrapotassic intrusive rocks post-date the ~60-55Ma collisional event between the Indian and the Asian continents. They are characterized by: (1) enrichment in large-ion lithophile elements and light rare-earth elements with (La/Sm)n =3.15-7.15; (2) strong positive Pb spikes; (3) depletion in high-field-strength elements (e.g. Nb/La=0.08-0.98); (4) high initial 87Sr/86Sr (0.706-0.709) with negative eNd(t) values of -10.5 to -0.9; (5) old Nd model ages of 1542-945Ma; and (6) radiogenic (207Pb/204Pb)i of 15.57-15.70 and (208Pb/204Pb)i (38.70-39.06). These features suggest that the mantle source was metasomatized by Proterozoic subduction beneath the Yangtze Craton. The lamprophyres have similar trace element patterns, and Sr-Nd-Pb isotope compositions, as coeval mafic lava, indicating a common source of metasomatized veined continental lithospheric mantle (CLM). Lower degree partial melting of metasomatic veins likely generated the lamprophyres, whereas the coeval mafic lava was likely derived from melting of phlogopite harzburgite. The lamprophyres and mafic lava have similar Sr-Nd isotope systematics as CLM-derived Neoproterozoic mafic rocks and Late Permian Emeishan low-Ti basalt in the region, indicating that they share the same Proterozoic source. We envisage that mantle plumes thermally eroded the Proterozoic metasomatized CLM beneath the western part of the Yangtze Craton during 825-750Ma and 260-250Ma, although residual metasomatized domains remained before being tapped by delamination after the India-Asia continental collision during the Paleogene period.